Genetically determined pattern of left ventricular function in normal and hypertensive hearts. Issue 5 (9th May 2018) - Kovács, Attila; Molnár, Andrea Ágnes; Kolossváry, Márton; Szilveszter, Bálint; Panajotu, Alexisz; Lakatos, Bálint Károly; Littvay, Levente; Tárnoki, Ádám Domonkos; Tárnoki, Dávid László; Voros, Szilard; Jermendy, György; Sengupta, Partho P.; et al.
Abstract : We sought to assess the inheritance of left ventricular (LV) function using speckle‐tracking echocardiography and the impact of hypertension on modifying the genetically determined pattern of contraction in a population of twins. We recruited 92 Caucasian twin pairs, including 74 hypertensive (HTN) siblings. Beyond standard echocardiographic protocol, a speckle‐tracking analysis was performed, including global longitudinal strain (GLS). Systolic function, as assessed by ejection fraction, showed moderate heritability (61%); however, GLS showed higher and dominant heritability (75%). Heterogeneity models revealed that there were no differences between the HTN and non‐HTN subjects regarding the heritability of GLS. However, the heritability estimates of diastolic function parameters, including early diastolic strain rate, were low. LV systolic biomechanics is highly heritable. GLS shows dominant heritability, despite the presence of early‐stage hypertensive heart disease. Early diastolic parameters are rather determined by environmental factors. These findings suggest the presence of a genetic framework that conserves systolic function despite the expression of diastolic dysfunction and may underlie the phenotypic progression towards heart failure with preserved ejection fraction.